Too enthusiastic to care for safety: Present status and recent developments of nanosafety in ASEAN countries - Karim, M.E. (Elsevier, 2015)
Nanotechnology has the prospect to vibrate the imagination of human being and has the ability to be used in almost every sector of human need. With its limitless potentials, there are many environmental, health and safety related concerns due to extremely ambivalent effects of nanoparticles. Studies revealed that nanoparticles can enter the human body through the lungs, intestinal tract, and skin. Therefore, the researchers and workers who handle nanoparticles and nanomaterials can theoretically and primarily be affected,whereas on the consumers this will have secondary effects. This paper aims at sharing and evaluating the investment scenario, present status and recent developments in nanotechnology, with specific focus on nanosafety issues in different research projects and national nanotechnology policies, strategies or roadmap in 6 ASEAN countries i.e. Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam. In general, it can safely be inferred that like their western counterparts, though these ASEAN countries have realized the importance of investment and institutional set-ups, and already spent huge amount of money in nanotechnology, the concern for nano risk and safety is not still considered a serious issue for them. This paper provides a better understanding and highlights the importance of prioritizing nanosafety issue to the policymakers and the stakeholders of this region.